Notes on Some Problems in the Aramaic Text of the Hadd-Yithʿi Bilingual - Gropp, Douglas M. (Bulletin of ASOR, 1985)
While the Aramaic of the Hadd-yithʿi bilingual shares some orthographic and grammatical features, as well as lexical items, with other Old Aramaic inscriptions, it also manifests some striking deviations. This paper discusses problems in the Aramaic text largely from a historical-grammatical viewpoint. Attention is given to the technique of the Aramaic translation, which evinces a developed translation tradition and displays a large degree of autonomy from the Akkadian original. The surprisingly early and full use of internal matres lectionis in this text is discussed, with its possible implications for understanding the origin of the system. Finally, a solution to the enigma of the composite character of the inscription is proposed.